The changing world of food packaging [ - Baricevic, Thomas; De Robbio, Michael; Dunn, Andrew (Classroom Video, 2010)
"In this Australian-made, curriculum fit program we visit packaging manufacturers - Visy Packaging and Recycling and Vision Pack - in our quest to understand the ins and outs of food packaging. We begin by explaining why food is packaged and outlining the advantages and disadvantages of traditional metal, glass, cardboard and foil packaging. We then examine the impact of changing consumer demands on packaging trends and continue with a detailed exploration of modern plastic packaging, modified atmosphere packaging and aseptic packaging. We conclude with a special insight into the development of new sustainable packaging, such as the starch-based 'Plantic', which can be composted at home"--Container.